Tae-miR397 Negatively Regulates Wheat Resistance to Blumeria graminis - Yuanyuan Guan; Zhiyuan Wei; Luyi Zhou; Kaige Wang; Meng Zhang; Puwen Song; Ping Hu; Haiyan Hu; Chengwei Li (Plants, 2023)
MicroRNA (miRNA) plays a crucial role in the interactions between plants and pathogens, and identifying disease-related miRNAs could help us understand the mechanisms underlying plant disease pathogenesis and breed resistant varieties. However, the role of miRNA in wheat defense responses remains largely unexplored. The miR397 family is highly conserved in plants and involved in plant development and defense response. Therefore, the purpose of this study was to investigate the function of tae-miR397 in wheat resistance to powdery mildew. The expression pattern analysis revealed that tae-miR397 expression was higher in young leaves than in other tissues and was significantly decreased in wheat Bainong207 leaves after Blumeria graminis (Bgt) infection and chitin treatment. Additionally, the expression of tae-miR397 was significantly down-regulated by salicylic acid and induced under jasmonate treatment. The overexpression of tae-miR397 in common wheat Bainong207 enhanced the wheat’s susceptibility to powdery mildew in the seedling and adult stages. The rate of Bgt spore germination and mycelial growth in transgenic wheat plants overexpressing tae-miR397 was faster than in the untransformed wild-type plants. The target gene of tae-miR397 was predicted to be a wound-induced protein (Tae-WIP), and the function was investigated. We demonstrated that silencing of Tae-WIP via barley-stripe-mosaic-virus-induced gene silencing enhanced wheat’s susceptibility to powdery mildew. qRT-PCR indicated that tae-miR397 regulated wheat immunity by controlling pathogenesis-related gene expressions. Moreover, the transgenic plants overexpressing tae-miR397 exhibited more tillers than the wild-type plants. This work suggests that tae-miR397 is a negative regulator of resistance against powdery mildew and has great potential for breeding disease-resistant cultivars.